Monitoring tensile fatigue crack growth and fiber failure around a notch in laminate SIC/SIC composites utilizing acoustic emission, electrical resistance, and digital image correlation. Issue 2 (February 2019) - Morscher, Gregory N.; Maxwell, Ryan
Abstract: Acoustic emission, electrical resistance, and surface optical techniques were used to monitor matrix cracking and fiber-breakage during fatigue in tension for [0/90]2s SiC-based laminate composite single-notch specimens. Acoustic emission sensors were positioned in several locations including on the edge of the specimen which enabled location of events through the width and the location of internal tunnel-type cracks. Surface optical techniques, including digital image correlation, enabled the extent of surface crack growth. From these two sets of data a simple circuit could be constructed of the different damaged and undamaged regions in the region of the notch that was in good agreement with the change in electrical resistance, thus establishing a correlation with change in ER and damage development. The unique placement of AE sensors on the edge of the specimen also enabled the capture and location of what are believed to be fiber failure events prior to ultimate failure.